Dental caries patterns and oral health behaviors in Arizona infants and toddlers - Douglass JM, Tinanoff N, Tang JMW, Altman DS (Blackwell Synergy, 2001)
The aim of this study was to use tooth eruption sequence, and a tooth- and surface-specific caries analysis method to determine: (1) the temporal relationship between tooth eruption and caries onset; (2) the validity of pre-existing concepts of caries progression; and (3) the relationship of certain putative health behaviors with caries prevalence.